2011
DOI: 10.1093/nar/gkr1017
|View full text |Cite
|
Sign up to set email alerts
|

Pseudouridine synthase 1: a site-specific synthase without strict sequence recognition requirements

Abstract: Pseudouridine synthase 1 (Pus1p) is an unusual site-specific modification enzyme in that it can modify a number of positions in tRNAs and can recognize several other types of RNA. No consensus recognition sequence or structure has been identified for Pus1p. Human Pus1p was used to determine which structural or sequence elements of human tRNASer are necessary for pseudouridine (Ψ) formation at position 28 in the anticodon stem-loop (ASL). Some point mutations in the ASL stem of tRNASer had significant effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 61 publications
(128 reference statements)
3
17
0
Order By: Relevance
“…Sibert and Patton determined a K d of 240 nM for the interaction between human Pus1 and tRNA Ser . 17 Affinities for the interaction between S. cerevisiae Pus1 to substrate tRNAs varied from 15 nM to 150 nM. 35 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sibert and Patton determined a K d of 240 nM for the interaction between human Pus1 and tRNA Ser . 17 Affinities for the interaction between S. cerevisiae Pus1 to substrate tRNAs varied from 15 nM to 150 nM. 35 …”
Section: Resultsmentioning
confidence: 99%
“…In a recent study Sibert and Patton analyzed the structural and sequence requirements of human Pus1. 17 A minimal substrate was identified that consists of the ASL and the TΨC-loop of tRNA Ser . While base pair interactions 3′ to the modification site in the ASL are critical for activity; hPus1 does not display specific sequence requirements in the TΨC-loop.…”
Section: Introductionmentioning
confidence: 99%
“…Pus1p modifies positions 27, 28 in the anticodon stem of many tRNAs, positions 34, 36 in certain tRNA introns, position 1 in tRNA Arg , and position 44 in U2 snRNA. Yeast Pus1p can also pseudouridylate tRNA positions 26, 65 and 67 in vivo , whereas human and mouse tRNAs lack Ψ at these positions (Sibert and Patton, 2012 and references therein). The site in U2 snRNA modified by Pus1p, U2-Ψ44, does not contain sequence elements in common with the tRNA substrate sites (Massenet et al, 1999), although this region is now known to form a stem in the branch-recognition stemloop (BSL) in one U2 conformation (Perriman and Ares, 2010), and this may present a substrate structure more analogous to tRNA than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…Such properties should intensify the interest in human C synthases, of which only hPus1p is characterized 109,111 and all others lack evidence on protein level (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
“…108 This difference in structure results in substrate specificity for a minimal substrate defined solely by shape and not by sequence. 109 In contrast, Pus7p acts on a specific recognition sequence. 102 This striking difference in substrate recognition could be confirmed in pseudouridine profiling of mRNA.…”
Section: Enzymatic Formation Of C Residuesmentioning
confidence: 99%